Clinical and angiographic characteristics of patients with coronary ectasia in a reference hospital - Rodríguez Falla, David Alejandro (2022)
Objective: To analyze the clinical and angiographic characteristics of patients with coronary ectasia found on coronary angiography. Materials and methods: Descriptive study of patients admitted to the cardiac catheterization laboratory of the Hospital Guillermo Almenara with coronary ectasia, during the years 2012 to 2020. The frequency of coronary ectasia, clinical, angiographic and coronary flow characteristics were determined. Results: 7504 catheterizations were reviewed, and 91 patients were found to have coronary ectasia (1.21%). Of these patients, 71 cases were male (78%), and the mean age was 67.74 ± 9.9 years. The 38.5% of cases were obese or overweight; 39.6% were hypertensive; 11% diabetic; 13.2% smoked; 3.3% had chronic kidney disease and 3.3% had polyglobulia. Sixty-one percent of cases had a diagnosis of acute coronary syndrome, and 24% of cases had high-risk stable angina. The artery most frequently involved by ectasia was the right coronary artery (70%). The average diameter of the ectatic artery was 5.7 mm. Occlusive thrombus was found in 19.8% of cases. There was a significant association between TIMI flow and diameter of the ectatic artery (p=0.000), and there was also an association between coronary ectasia and acute coronary syndrome among patients living at an altitude of more than 2500 m (p=0.000). Conclusions: coronary ectasia was an infrequent entity among patients who underwent coronary angiography, was predominantly male, mainly involved the right coronary artery, was associated with lower TIMI flow, and acute coronary syndrome among residents above 2500 m of altitude.